The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/s2214-109x(20)30311-9
|View full text |Cite|
|
Sign up to set email alerts
|

The health and economic burden of smoking in 12 Latin American countries and the potential effect of increasing tobacco taxes: an economic modelling study

Abstract: Background Worldwide, smoking tobacco causes 7 million deaths annually, and this toll is expected to increase, especially in low-income and middle-income countries. In Latin America, smoking is a leading risk factor for death and disability, contributes to poverty, and imposes an economic burden on health systems. Despite being one of the most effective measures to reduce smoking, tobacco taxation is underused and cigarettes are more affordable in Latin America than in other regions. Our aim was to estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 19 publications
0
51
1
10
Order By: Relevance
“…In fact, a ban on advertising should be used in the context of other measures. In other studies, our group estimated the health and cost effects of applying tax increase, plain packaging, and smoke-free strategies in the region and found that the first strategy had the most significant effect [ 22 , 25 , 44 , 45 ]. However, as it occurs with the other measures, the effects of a comprehensive ban on tobacco advertising and sponsorship would result in important health benefits and savings for the health systems in the region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, a ban on advertising should be used in the context of other measures. In other studies, our group estimated the health and cost effects of applying tax increase, plain packaging, and smoke-free strategies in the region and found that the first strategy had the most significant effect [ 22 , 25 , 44 , 45 ]. However, as it occurs with the other measures, the effects of a comprehensive ban on tobacco advertising and sponsorship would result in important health benefits and savings for the health systems in the region.…”
Section: Discussionmentioning
confidence: 99%
“…The smoking burden model allows for the estimation of health and economic impact of tobacco, at present and after implementation of interventions to reduce smoking prevalence. This model has been validated and applied in studies carried out in 12 Latin American countries that estimated the burden of disease and the expected impact of tobacco tax increases and other strategies [ 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Institute for Clinical Effectiveness and Health Policy (IECS) coordinated a multi-country initiative to develop an economic model to estimate the tobacco-related disease and economic burden and evaluate the impact of different tobacco control interventions, including taxation, cigarette plain packaging, advertising, and smoke-free environments [ 7 ]. This model has been applied in several studies to estimate the burden of smoking and the potential impact of tobacco control interventions in different countries [ 8 – 13 ].…”
Section: Methodsmentioning
confidence: 99%